K-Pop Idols’ Marketing Magic: Boosting Healthy Product Purchases through Brand Ambassador - Fitriani, Adjeng Dwi; Pramesthi, Hanum Kanthi; Prasetyo, Bambang Dwi; Muchtar, Moch. Shobastian Mahendra (Universitas Brawijaya, 2024)
This study aims to determine how the influence of K-Pop idol NCT Dream as a brand ambassador on purchasing decisions for Lemonilo instant noodle products. The population in this study were followers of the @NCTDreamINA Twitter account and used purposive sampling by distributing questionnaires to 100 respondents with the criteria of citizens aged 15-25 years, NCT Dream fans who have purchased Lemonilo x NCT Dream instant noodle products, and followers of the @NCTDreamINA Twitter account. The results of this study prove that the NCT Dream brand ambassador has a significant or positive influence on purchasing decisions on Lemonilo instant noodle products. When associated with ELM theory, persuasive communication carried out by Lemonilo is a peripheral route, namely displaying various interactive content and promotion of Lemonilo advertisements on social media by showing NCT Dream as a brand ambassador.